2023
DOI: 10.3390/molecules28083618
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and Stability of Carotenoids in Ammonium- and Phosphonium-Based Ionic Liquids: Effect of Solvent Nature, Temperature and Water

Abstract: Ionic liquids (ILs) have arisen as alternatives to organic solvents and been used in natural pigment extraction in recent decades. However, the solubility and stability of carotenoids in phosphonium- and ammonium-based ILs are insufficiently explored. In this work, the physicochemical properties of the ILs, and the dissolution behavior and storage stability of three carotenoids (astaxanthin, β-carotene, and lutein) in the IL aqueous solution were investigated. The results showed that the solubility of the caro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…It was found that higher carotenoid content was in the medium supplied with lower ammonium concentration and at the early growth stages (Figure 3). Cheng et al (2023) reported that ammonium ions reacted with other antioxidant compounds including carotenoids. The finding suggested that ammonium-free medium or lower ammonium concentration can be a possible strategy to enhance the high carotenoid accumulation in higher plants.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that higher carotenoid content was in the medium supplied with lower ammonium concentration and at the early growth stages (Figure 3). Cheng et al (2023) reported that ammonium ions reacted with other antioxidant compounds including carotenoids. The finding suggested that ammonium-free medium or lower ammonium concentration can be a possible strategy to enhance the high carotenoid accumulation in higher plants.…”
Section: Discussionmentioning
confidence: 99%
“…The EAst was increased as the IL content increased, and the maximum recovery of 32.50 µg/g and 25.28 µg/g could be obtained when the [P4444]CF3COO and [P4448]CF3COO content reached 40%. It is probably that the increase of IL concentration would increase the solubility of Ast, which was beneficial to the extraction of Ast [39,41,42]. However, higher viscosity of the IL could limit the efficiency of mass transfer [43].…”
Section: Effect Of Il Contentmentioning
confidence: 99%